Speech Act of Requests Found in Different Rating Films - Amelia, Firqo; Firdaus, Ahmad Yusuf (Universitas Swadaya Gunung Jati, 2018)
This study aims to find the forms of strategies and functions of requests in English that are used in several films with different ratings. Another objective of this research is to find the relations between the uses of strategies and functions of requests in English. Film is a picture of everyday life and we can see the cultures of a society, one of which is the use of language. To view the request speech acts in English, then two films that use English as a communication tool with regard to the different ratings were selected. The selection of films with different ratings are intended to see differences in the use of language in movies watched by children and adolescents. Rating in the selected movie consists of G (general audiences) and PG (parental guide suggested). Rating G is a film that is for the public, which means that the film can be watched by all ages. Rating PG is a movie that can be watched by children under parental guidance. Having found the forms and strategies of request speech acts in different films with different ratings, the situations and conditions of the use and the functions of request strategies were identified. Forms of speech act strategies invoked were classified based on the theory advanced by Trosborg (1995), while to see the functions of request speech acts Tsui’s Theory (1994) was used. As for achieving the objectives of this study, the authors use several effective methods. In collecting the data, the techniques used were watching and listening to the films that have been selected. Then recorded phrases of request speech acts found in the films. Once collected, the data were analyzed by using analysis technique proposed by Spradley (1980), ie domain analysis, taxonomic, componential and cultural value. From the analysis, it was concluded that there was no difference in strategies and functions used in the two films. Both use four strategies, namely indirect request, the hearer-oriented condition, speaker-based condition, and direct request. In addition, they also illustrate the same five functions of request speech acts, request for action, request for permission, offer, invitation, and proposal. The most frequently used strategy and function are direct request and request for action respectively.